E. Fromm’s Concept of Man and His Authentic Life in Society (II) - Jekentaitė, Leonarda (Problemos, 1981)
The concept of individual depersonification suggested by E. Fromm in his works and taken as principle of his criticism against modem bourgeois society, is discussed in the second part of the article. The utopian character of E. Fromm’s society improvement plans that take of radical social changes to transformation of separate individuals is revealed.